Evaluating the Impact of Hybrid Electronic-paper Environments Upon Novice Nurse Information Seeking - Borycki, E. M.; Lemieux-Charles, L.; Nagle, L.; Eysenbach, G. (Methods of Information in Medicine, 2009)
Objective: The purpose of this study was to investigate the effects of hybrid environments (i.e. where part of the patient record is paper-based and part of it is electronic) upon aspects of novice nurse information seeking (i.e. amount of information accessed, choice of key information sources, type of information and use of information seeking tactics).Methods: A within group, laboratory, experimental study was conducted using two simulated environments (i.e. a paper environment and a hybrid environment). Thirty-five novice nurses participated in the study.Results: Findings revealed significant differences between the paper and hybrid environments in terms of their effects upon aspects of novice nurse information seeking. Subjects accessed: 1) less information in the hybrid environment than the paper environment, 2) more non-electronic sources of information were accessed by novice nurses in the hybrid environment, and 3) novice nurses used more passive information seeking tactics in the hybrid environment than the paper environment. Qualitative findings from the cued recall data revealed subjects experienced increased cognitive load in the hybrid environment.Conclusions: Hybrid environments may affect aspects of novice nurse information seeking. Future research should explore the effects of hybrid environments upon the information seeking of other types of health professionals (e.g. physicians, physiotherapists) with differing levels of expertise (i.e. novice, intermediate and expert).
Keywords: EPR; CPR; EMR; EHR; human factors; hybrid; electronic-paper; environment; novice; nurse; health professional; information seeking; information needs